PHP programming with my SQL - Gosselin, Don (Thomson Course Technology, 2006)
PHP Programming with MySQL, by Don Gosselin is the first true academic textbook in the market to combine PHP with MySQL. This book covers one of the fastest growing technology combinations for developing interactive Web sites. With growth attributed to its open-source nature and usability amongst non-programmers, this text is accessible to users with little programming or database experience and suits personal Web development projects, as well as small to medium business Web development needs.